2023
DOI: 10.3390/plants12183232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Common Biochar and Acid-Modified Biochar on Growth and Quality of Spinach in Coastal Saline Soils

Juan Wang,
Danyi Shi,
Chengzhen Huang
et al.

Abstract: The rational development and efficient utilization of saline soils can alleviate the problem of insufficient arable land faced by agricultural production in China. A prominent problem is improving soil salt and water conditions for promoting land resources’ productivity in coastal areas. Biochar is widely used for soil improvement, as it has remarkable properties. A pot experiment was conducted to study the effects of two kinds of biochar (common biochar and acid-modified biochar) with three addition rates (2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In the bio-organic fertilizer group, the greatest ET, yield and water productivity were obtained under B1Ft, and the peak WP was also observed under B1Fc in the compound fertilizer group, which indicates that there is a threshold of biochar addition and that excessive biochar addition is uneconomical and less effective. A similar conclusion was also reached by Huang [31], who reported that the water use efficiency significantly improved under low and medium biochar addition rates, and there was no help when the addition rate reached 8%. Zhuang [32] also reported that at the same N fertilizer application amount, the dry matter accumulation of plants first increased and then decreased with increasing biochar addition rate, and a moderate increase of 4% was a reasonable amount combined with N fertilizer application.…”
Section: Accumulated Irrigation Water Amount and Water Productivitysupporting
confidence: 81%
See 1 more Smart Citation
“…In the bio-organic fertilizer group, the greatest ET, yield and water productivity were obtained under B1Ft, and the peak WP was also observed under B1Fc in the compound fertilizer group, which indicates that there is a threshold of biochar addition and that excessive biochar addition is uneconomical and less effective. A similar conclusion was also reached by Huang [31], who reported that the water use efficiency significantly improved under low and medium biochar addition rates, and there was no help when the addition rate reached 8%. Zhuang [32] also reported that at the same N fertilizer application amount, the dry matter accumulation of plants first increased and then decreased with increasing biochar addition rate, and a moderate increase of 4% was a reasonable amount combined with N fertilizer application.…”
Section: Accumulated Irrigation Water Amount and Water Productivitysupporting
confidence: 81%
“…On the other hand, due to its huge specific surface area, biochar can also improve soil structure and provide growth space for soil microorganisms, promote microbial activity, contribute to the decomposition and transformation of organic fertilizer, and release more nutrients for crops to absorb [25]. The plant growth-promoting effects of biochar were also reported for spinach by Wang et al [26]. Wu et al [27] revealed that soybean growth and yield were significantly improved by biochar addition.…”
Section: Growth and Yieldmentioning
confidence: 99%
“…However, the material and pyrolysis temperature have the greatest influence on the effects of biochar 16 . Biochar addition to the soil increases its pH and improves nutrient availability and uptake by plants 17 . For example, biochar increases the availability of fixed phosphorous with high contents of aluminum (Al 3+ ) and iron (Fe 2+ ) under acidic conditions 18 , and improves the bioavailability of nitrogen (N), phosphorous (P), potassium (K), Ca 2+ , and Mg 2+ 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Degraded vegetation exacerbates intertidal surface exposure, and sunlight exposure will exacerbate the salinization of intertidal soils, destroying the ecological function of soils and damaging microbial environments [ 2 , 3 ]. It could ultimately transform the coastal soil environment into salting beaches with low plant diversity [ 4 , 5 ]. Furthermore, the degradation of vegetation also leads to a decrease in the ability of the intertidal zone to absorb pollutants and heavy metals in the sedimentary environment, which exacerbates environmental pollution in the intertidal zone.…”
Section: Introductionmentioning
confidence: 99%